2015
DOI: 10.5539/eer.v5n1p33
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact Analysis of the Emission from Petroleum Refineries in Nigeria

Abstract: Health and environmental hazards, a thing of global concern have been the major characteristics of the petroleum refinery areas worldwide, Nigeria inclusive. This is as a result of the emissions from petroleum refineries which resulted into air quality degradation of the host environment. This problem which has equally affected the climatic conditions of the petroleum producing areas is more pronounced in Nigeria due to lack of implementing adequate policies to protect the host environment. This study is carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Through regular emissions, fugitive releases, unintentional releases, or plant upsets from various refining operations such separation, conversion, and treatment processes, several contaminants are released into the environment [13]. As a result of equipment malfunction, pipeline deterioration, and other factors, almost 900 accidents involving oil refining and exploration were reported in Nigeria in 2000 [14]. According to earlier research, criteria pollutants can harm plants and humans by causing DNA deterioration in bone marrow cells, respiratory illnesses, and decreased lung function in people [15], and the production of acid rain, which degrades water quality and affects aquatic habitat.…”
Section: Health Safety and Environmental Implications Of Oil And Gas ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Through regular emissions, fugitive releases, unintentional releases, or plant upsets from various refining operations such separation, conversion, and treatment processes, several contaminants are released into the environment [13]. As a result of equipment malfunction, pipeline deterioration, and other factors, almost 900 accidents involving oil refining and exploration were reported in Nigeria in 2000 [14]. According to earlier research, criteria pollutants can harm plants and humans by causing DNA deterioration in bone marrow cells, respiratory illnesses, and decreased lung function in people [15], and the production of acid rain, which degrades water quality and affects aquatic habitat.…”
Section: Health Safety and Environmental Implications Of Oil And Gas ...mentioning
confidence: 99%
“…It further stated that due to its function as a supplier of transportation fuels and chemicals, the worldwide refining sector increased its capacity by 13% from 2000 to 2018, leading to a total GHG increase of 24% [18]. A study on the environmental impact assessment on Nigeria refineries by [14] explained that results from the emission inventory showed that refinery is one of the major sources of air pollution in Nigeria. The environmental and health impacts of these pollutants indicate that adequate control has to be put in place, as more refineries are established, to ensure reduction in the emissions.…”
Section: Health Safety and Environmental Implications Of Oil And Gas ...mentioning
confidence: 99%
“…The refining process releases pollutants into the air. When converting crude oil into petroleum products, wastes of different kinds are generated when equipment leaks, combustion of fuels, heating of steam and process fluids, and the transfer of products (Oladimeji et al, 2015). Pollutant emissions are severe enough to be observed from space.…”
Section: Refinery Pollution Outages and Regulationmentioning
confidence: 99%